Is It Necessary to Specifically Define the Cause of Surgically Treated Biliary Tract Infections? A Rare Case of Raoultella planticola Cholecystitis and Literature Review - Suat Can Ulukent; İnanc Samil Sarici; Nuri Alper Sahbaz; Yigit Mehmet Ozgun; Ozlem Akca; Kamuran Sanlı (Case Reports in Infectious Diseases)
Raoultella planticola is an aquatic and soil organism that does not notoriously cause invasive infections in humans. Infections in the literature are limited only in case reports. We present a very rare case of R. planticola cholecystitis. A 71-year-old female patient with abdominal pain was diagnosed with acute cholecystitis. Patient received intravenous antibiotic treatment, but the treatment failed and the patient underwent an open cholecystectomy. The final pathological result was gangrenous cholecystitis complicated with R. planticola. Eventually, the patient recovered with appropriate antimicrobial therapy. Patients with acute cholecystitis are usually treated without any microbiological sampling and antibiotic treatment is started empirically. To date, there have only been 5 reported biliary system related R. planticola infections in humans. We believe that Raoultella species might be a more frequent agent than usually thought, especially in resistant cholecystitis cases. Resistant strains should be considered as a possible causative organism when the patient’s condition worsened despite proper antimicrobial therapy. It should be considered safe to send microbiological samples for culture and specifically define the causative microorganisms even in the setting of a cholecystectomized patient.